Does Financial Technology Lending and Financial Literacy Affect Crime? Evidence From Indonesia - Nugraha, Handy; Putriani, Santi; Febriani, Hanifah; Kuncoro, Trian Gigih; Anas, Muhammad; Puspitasari, Inda Fresti (Universitas Muhammadiyah Malang, 2024)
Purpose: This research aims to investigate the relationship between FinTech Lending and Financial Literacy on Crime (fraud, embezzlement, and corruption). This research provides knowledge about the impact of FinTech Lending which can increase crime and financial literacy which can reduce crime. Methodology/approach: This study employs panel data consisting of 34 provinces in Indonesia with observations in 2019 and 2022 due to data availability. The secondary data used was collected from official Indonesian government institutions (OJK and BPS). To achieve the purpose, a quantitative approach and panel data regression analysis methods are applied. Panel data provides more variability, less collinearity among variables, and more degrees of freedom. This can lead to more efficient estimators and more precise inference of model parameters. Based on the Hausman test, the estimated model is Random Effects (RE). Findings: The results of this research show that FinTech Lending has a significant positive impact on the growth of crime, while Financial Literacy has a negative impact on the growth of crime. This indicates that as the use of FinTech Lending increases, crime rates also increase, and higher levels of Financial Literacy help reduce the growth of crime. Practical implications: The results of this research can be used as material for consideration by the government in creating a comprehensive legal framework through the establishment of a Law on FinTech. Originality/value: To the best of the researcher's knowledge, this research is the first research to investigate the influence of FinTech Lending and Financial Literacy on Crime Rates in Indonesia using a quantitative approach, whereas previous research used a qualitative approach.